2019
DOI: 10.1016/j.jtcvs.2018.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating benign from malignant cardiac tumors with cardiac magnetic resonance imaging

Abstract: Background: The purpose of this analysis is to describe the differences in cardiac magnetic resonance characteristics between benign and malignant tumors, which would be helpful for surgical planning.Methods: This was a prospective cohort study of 130 patients who underwent cardiac magnetic resonance imaging for evaluation of a suspected cardiac mass. After excluding thrombi and tumors without definitive diagnosis, 66 tumors were evaluated for morphologic features and tissue composition.Results: Of the 66 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 20 publications
(29 reference statements)
2
33
0
5
Order By: Relevance
“…CMR is the best imaging modality for evaluating cardiac masses and differentiating inflammation from cardiac metastases. Moreover, it can distinguish between thrombus and cardiac tumors and is an invaluable non-invasive method for differentiating malignant and benign cardiac tumors [13]. The imaging characteristics that are useful for the differentiation are tumor size, invasion of the free wall or adjacent structure, and first-pass perfusion to determine tumor's vascularity [13].…”
Section: Discussionmentioning
confidence: 99%
“…CMR is the best imaging modality for evaluating cardiac masses and differentiating inflammation from cardiac metastases. Moreover, it can distinguish between thrombus and cardiac tumors and is an invaluable non-invasive method for differentiating malignant and benign cardiac tumors [13]. The imaging characteristics that are useful for the differentiation are tumor size, invasion of the free wall or adjacent structure, and first-pass perfusion to determine tumor's vascularity [13].…”
Section: Discussionmentioning
confidence: 99%
“…We find cardiac magnetic resonance imaging particularly helpful, because it can establish the presence or absence of perfusion in most cases. 4 A cardiac magnetic resonance imaging study in this case might or might not have shown perfusion, because hematomas have no perfusing vessels, but there did appear to be some sinuses of perfusion in the mass. If clinical information and imaging suggest that this is a potential tumor, then the treatment pathway should also be of interest to cardiac surgeons.…”
mentioning
confidence: 84%
“…While the imaging characteristics, as described above, of myxomas are often diagnostic, unusual appearing masses might prompt further imaging to rule-out other tissue types. The differential diagnosis for such masses includes teratomas (rare), lipomas, angiosarcomas, rhabdomyomas, and rhabdomyosarcomas [18]. Distinguishing characteristics often consist of intramyocardial tumor invasion on imaging.…”
Section: Myxomasmentioning
confidence: 99%